Parachuting from fixed objects: descriptive study of 106 fatal events in BASE jumping 1981–2006. Issue 6 (3rd June 2008) - Westman, A; Rosén, M; Berggren, P; Björnstig, U
Abstract : Objective: To analyse the characteristics of fatal incidents in fixed object sport parachuting (building, antenna, span, earth (BASE) jumping) and create a basis for prevention. Design: Descriptive epidemiological study. Participants: Data on reported fatal injury events (n = 106) worldwide in 1981–2006 retrieved from the BASE fatality list. Assessment of risk factors: Human, equipment and environmental factors. Main outcome measurements: Identification of typical fatal incident and injury mechanisms for each of the four fixed object types of BASE jumping (building, antenna, span, earth). Results: Human factors included parachutist free fall instability (loss of body control before parachute deployment), free fall acrobatics and deployment failure by the parachutist. Equipment factors included pilot chute malfunction and parachute malfunction. In cliff jumping (BASE object type E), parachute opening towards the object jumped was the most frequent equipment factor. Environmental factors included poor visibility, strong or turbulent winds, cold and water. The overall annual fatality risk for all object types during the year 2002 was estimated at about one fatality per 60 participants. Conclusions: Participants in BASE jumping should target risk factors with training and technical interventions. The mechanisms described in this study should be used by rescue units to improve the management of incidents.